PGMK (Pendidikan Generasi Muda Kepramukaan) sebagai Model Experiential Civic Learning dalam Penguatan Civic Skills Mahasiswa PPKn UNNES - Millati Islamia Hanifa; Fadli Awaludin; Shelly Saputri; Bilal Azril Pratama; Dias Suci Hasanah (INDO PUBLISHING, 2026)
Globalization requires students not only to master academic knowledge but also to develop civic skills such as leadership, teamwork, responsibility, and social empathy. However, Civics Education (PPKn) learning that is still dominated by cognitive aspects often results in the low application of civic skills in real-life situations. This study aims to analyze the role of Youth Education and Scouting (PGMK) as an experiential civic learning model in strengthening the civic skills of PPKn students at UNNES. The research uses a qualitative method with a descriptive approach. Data were collected through literature review and analysis of PGMK implementation, which integrates both indoor and outdoor learning activities. The results show that PGMK provides direct learning experiences through leadership training, teamwork activities, and problem-solving exercises, thereby contributing to the strengthening of students’ civic skills. The experiential learning model within PGMK effectively bridges theoretical knowledge with real-world practice. Therefore, PGMK can serve as an innovative learning model to improve the quality of Civics Education in a more contextual and meaningful way.